The Influence of Alexithymia on Alcohol Craving, Health-Related Quality of Life and Gender in Alcohol-Dependent Outpatients. Issue 4 (7th August 2020) - Thorberg, Fred Arne; Hasking, Penelope; Huang, Ya-Ling; Lyvers, Michael; Young, Ross McD.; Connor, Jason P.; London, Edythe D.; Feeney, Gerald F. X.
ABSTRACT: Alexithymia is a vulnerability factor for physical and mental illness that can significantly influence the daily function of alcohol-dependent patients. The aim of this study was to examine the indirect effect of obsessive thoughts and compulsive behaviors involving alcohol craving on the relationship between alexithymia, quality of life (QoL) of psychological well-being and health status. Three hundred and eighty-one outpatients (263 males and 118 females) in treatment for alcohol dependence completed self-report measures of alexithymia, alcohol craving, GHQ-28 (QoL-psychological well-being) and SF-36 (QoL-health status). Males scored significantly higher than females on aspects of alexithymia, and females reported significantly higher levels of alcohol craving. Path analysis showed an indirect effect of alcohol craving on the relationship between alexithymia, QoL-psychological well-being and self-reported QoL-health status for males only. The current study provides important new information about impaired self-reported health status and well-being among male alcohol-dependent treatment seekers with alexithymia.